2008
DOI: 10.1186/1746-4269-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal plant knowledge and practice of the Oromo ethnic group in southwestern Ethiopia

Abstract: An ethnomedicinal study was conducted to document the indigenous medicinal plant knowledge and use by traditional healers in southwestern Ethiopia from December 2005 to November 2006. Data were collected from 45 randomly selected traditional healers using semi-structured interviews and observations. Sixty-seven ethnomedicinal plant species used by traditional healers to manage 51 different human ailments were identified and documented. Healers' indigenous knowledge was positively correlated with their reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
120
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(158 citation statements)
references
References 32 publications
29
120
4
1
Order By: Relevance
“…The majority of medicinal plants were collected from the wild which is consistent with many studies across Ethiopia (Cotton, 1996;Giday, 2001;Giday and Ameni, 2003;Yineger et al, 2008;Bekalo et al, 2009;Yirga, 2010b, c). Medicinal plants were also collected from caves and lakes mainly herbs and algae.…”
Section: Discussionsupporting
confidence: 53%
“…The majority of medicinal plants were collected from the wild which is consistent with many studies across Ethiopia (Cotton, 1996;Giday, 2001;Giday and Ameni, 2003;Yineger et al, 2008;Bekalo et al, 2009;Yirga, 2010b, c). Medicinal plants were also collected from caves and lakes mainly herbs and algae.…”
Section: Discussionsupporting
confidence: 53%
“…Other ethnomedicinal studies such as Amenu (2007), Yineger and Yewhalaw (2007), Yineger et al (2008), Mesfin et al (2009), Etana (2010, and Addisie et al (2012) also reported that leaves were the most commonly used plant parts in remedy preparations. This finding is inconsistent, however, with the result of Lulekal et al (2008) where roots were most used.…”
Section: Tass Parts Used To Treat Human Diseasesmentioning
confidence: 99%
“…Nevertheless, limited professionals have made an attempt to document medicinal TASS and traditional knowledge in some parts of Ethiopia. These include Giday (2001), Hunde (2001), Seifu (2004), Hunde et al (2006), Amenu (2007), Yineger and Yewhalaw (2007), Teklehaymanot and Giday (2007), Lulekal et al (2008), Yineger et al (2008), Mesfin et al (2009), Awas and Demissew (2009), Hailemariam et al (2009), Tamene et al (2009), Yirga (2010), Etana (2010), Hunde Feyssa et al (2011), Yirga et al (2011), Addisie et al (2012), Belayneh et al (2012), Megersa et al (2013), and Mesfin et al (2014) among others. Indeed, there is a need to do more in parts of the country where such studies have not been conducted due to the cultural diversity and the diverse flora of Ethiopia.…”
Section: Published: 22 June 2015mentioning
confidence: 99%
“…Age is another frequent factor analyzed in ethnobotanical studies; the elders tend to have more knowledge of medicinal plants (Quinlan & Quinlan 2007;Yineger et al 2008), although not in all cases (Yineger et al 2008;Da Silva & Proença 2008). According to Voeks (2007) people acquire more knowledge with age, which can explain the tendency of fi nding greater knowledge accumulation amongst the elders.…”
Section: Introductionmentioning
confidence: 99%